Scalp acupuncture regulates functional connectivity of cerebral hemispheres in patients with hemiplegia after stroke - Lin, Dan; Gao, Jinyang; Lu, Mengxin; Han, Xiao; Tan, Zhongjian; Zou, Yihuai; Cui, Fangyuan (Frontiers in Neurology, 2023)
Stroke is a common cause of acquired disability on a global scale. Patients with motor dysfunction after stroke reduced life quality and suffer from economic burden. Scalp acupuncture has been proven to be an effective treatment for motor recovery after stroke. However, the neural mechanism of scalp acupuncture for motor function recovery is unclear. This study aims to investigate functional connectivity (FC) changes of region-of-interest (ROI) and other brain regions to interpret the neural mechanism of scalp acupuncture.